Development of multi-beam trapping and sorting techniques using microoptical elements - Sun, Yuyang (2009)
The thesis provides a broad and systematic study on the micro-optical elements based multi-beam trapping and sorting techniques by means of theoretical formulations and experimental demonstrations. The optical sorting technique is not based on the tightly focused single-beam optical tweezers, but the periodical optical energy landscape. This all-optical sorting method does not rely on the fluorescent marker but on the intrinsic physical attributes such as geometrical size and refractive index. It is a passive continuous microfluidic sorting and requires no human interaction. The refractive and diffractive optical elements (DOE), including microlens arrays (MLA), Dammann gratings, holographic optical elements and chess-board gratings, are designed and fabricated to create array of optical traps. The multi-beam optical trapping and optical sorting have been demonstrated experimentally using MLA or DOE based lens projection trapping systems. The system requires minimum modification to traditional single-beam optical tweezers. All-optical on-chip optical sorting on periodical optical lattices is experimentally demonstrated using the Talbot effect and MLA respectively. It is further experimentally proved that the three-dimensional (3D) optical lattice generated by the modified Talbot effect can realize multi-level array trapping of particles. In addition, the 3D optical lattice is applied to the creation of 3D sub-micron sized periodical structures in polymer-dispersed liquid crystal (PDLC). The 3D optical lattice created by the modified Talbot effect has been demonstrated for the first time to be capable of simultaneous multilevel trapping of particles arrays. Based on this secondary layer-by-layer self-imaging effect, optical trapping of silica and polystyrene colloidal particles at different planes in a microchamber are demonstrated experimentally. The method requires no lens projection and the trapping range in both the axial and lateral direction may reach hundreds of micrometers. In addition, the created 3D optical lattice was also employed to realize a convenient one-step fabrication of 3D sub-micron sized periodical structure in PDLC. The fabricated sol-gel microlens array is also capable of realizing on-chip multiple optical trapping and optical sorting. The integrated optical trapping system is composed of a micro chamber and a designed MLA fabricated on a glass substrate. The on-chip multi-beam optical trapping and locked-in transport of particles are experimentally demonstrated within the micro chamber. The present research has successfully demonstrated the use of micro-optical elements and Talbot self-images effects for the generation of two-dimensional (2D) optical landscape and 3D optical lattices for the realization of 2D and 3D optical trapping and sorting of micro-particles.